La céramique non décorée de l’abri de Hassi Ouenzga et le début de l’utilisation des récipients en céramique dans le nord-ouest du Maghreb - Schneider, Florian (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
In the 1996–1997 excavations of the archaeological site Hassi Ouenzga Abri ceramic sherds were found in a layer, which was dated to 6800 B. C. cal. But although the stratigraphy of the site and the date seem to be sound there were still doubts concerning the age of those ceramic sherds. As there are also ceramics in the layer above, which was dated to 5500 B. C. cal., there remained the possibility that the ceramics were deplaced after deposition. Therefore the technological properties of the ceramics of those two layers were analysed and compared following the hypothesis that the ceramics are of a different age, if there are statistical signifi cant differences between the sherds of the two layers. The article will be available as a PDF in the near future.